2014
DOI: 10.3390/rs6065541
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Trends in Light Pollution in China Based on Nighttime Satellite Imagery

Abstract: China is the largest developing country worldwide, with rapid economic growth and the highest population. Light pollution is an environmental factor that significantly influences the quality and health of wildlife, as well as the people of any country. The objective of this study is to model the light pollution spatial pattern, and monitor changes in trends of spatial distribution from 1992 to 2012 in China using nighttime light imagery from the Defense Meteorological Satellite Program Operational Linescan Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…The results supported the hypothesis of regional favoritism that some political leaders may make political decisions beneficial to their birth regions. Other examples can be found in modeling in-use steel stock in buildings and civil engineering infrastructure [86], monitoring trend of light pollution [87][88][89][90] and evaluating global armed conflicts [18,40,91].…”
Section: Major Challengesmentioning
confidence: 99%
“…The results supported the hypothesis of regional favoritism that some political leaders may make political decisions beneficial to their birth regions. Other examples can be found in modeling in-use steel stock in buildings and civil engineering infrastructure [86], monitoring trend of light pollution [87][88][89][90] and evaluating global armed conflicts [18,40,91].…”
Section: Major Challengesmentioning
confidence: 99%
“…Therefore, light pollution trends can change drastically across different spatial scales [23]. However, in comparison to the ever-increasing amount of nighttime lighting in China, the specific and land use-oriented assessment and management of light pollution -and associated planning -are still underdeveloped [24].…”
Section: Introductionmentioning
confidence: 99%
“…IDA has suggested that zones with high levels of light should yield to zones with low levels of light [22]. The citizens of China's metropolises continue to suffer from severe light pollution, which demands prompt solutions [23]. For example, more than half of the citizens of Shenzhen have reported feeling uncomfortable due to light pollution [25]; and light intensity at night is more than 30 to 60 times higher than the acceptable standard in Guangzhou [26].…”
Section: Introductionmentioning
confidence: 99%
“…China has many different regions, each with its own socioeconomic and environmental characteristics [24], and even in the same city, different zones have different light levels and lighting criteria due to their different land use functions [25,26]. Therefore, light pollution trends can change drastically across different spatial scales [27]. However, in comparison to the ever-increasing amount of night-time lighting in China, the specific and land use-oriented assessment and management of light pollution and associated planning are still underdeveloped [28].…”
Section: Introductionmentioning
confidence: 99%
“…IDA (International Dark-Sky Association) has suggested that zones with high levels of light should yield to zones with low levels of light [26]. The citizens of China's metropolises continue to suffer from severe light pollution, which demands prompt solutions [27]. For example, more than half of the citizens of Guangzhou have reported feeling uncomfortable due to light pollution [29]; and LED (Light Emitting Diode) screen had influenced the daily life of the residents in Shenzhen [30].…”
Section: Introductionmentioning
confidence: 99%